2014
DOI: 10.1182/blood-2014-07-588046
|View full text |Cite
|
Sign up to set email alerts
|

PARP-14 combines with tristetraprolin in the selective posttranscriptional control of macrophage tissue factor expression

Abstract: Key Points This study has identified a novel mechanism by which TF expression is posttranscriptionally regulated in macrophages. The mechanism involves the control of mRNA stability by a cooperation between PARP-14 and TTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 54 publications
7
54
0
Order By: Relevance
“…The anti-inflammatory role of PARP14 reported by us are consistent with other reports. Iqbal et al (2014) demonstrated in macrophages that PARP14 reduces mRNA stability and thus expression levels of tissue factor, a surface glycoprotein that plays a major thrombogenic role in macrophage-rich atherosclerotic lesions. PARP14's association with anti-flammatory STAT6 was first described using a yeast two-hybrid screen (Goenka and Boothby 2006).…”
Section: Parp9 and Parp14 Regulate Macrophage Activationmentioning
confidence: 99%
“…The anti-inflammatory role of PARP14 reported by us are consistent with other reports. Iqbal et al (2014) demonstrated in macrophages that PARP14 reduces mRNA stability and thus expression levels of tissue factor, a surface glycoprotein that plays a major thrombogenic role in macrophage-rich atherosclerotic lesions. PARP14's association with anti-flammatory STAT6 was first described using a yeast two-hybrid screen (Goenka and Boothby 2006).…”
Section: Parp9 and Parp14 Regulate Macrophage Activationmentioning
confidence: 99%
“…Recent study also shows that ARTD8 is involved in mRNA stability. ARTD8 is found to form a complex with tristetraprolin (TTP) and 3’ untranslated region of mRNA, which suppresses the degradation of mRNA [88]. …”
Section: Adp-ribosyltransferasementioning
confidence: 99%
“…Previous reports indicated that PARP14 enhances IL-4-induced gene expression by interacting with the cytokine-induced signal transducer and activator of transcription 6 (STAT6) in B and T cells, thereby functioning as a transcriptional co-activator2526 that may mediate this effect. A recent study reported that PARP14 regulates the stability of tissue factor mRNA in M(LPS) in mouse27. Less information exists regarding the molecular function of PARP9/ARTD9.…”
mentioning
confidence: 99%